2004
DOI: 10.1111/j.1365-2419.2004.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Decadal changes in reproduction of walleye pollock (Theragra chalcogramma) off the Pacific coast of northern Japan

Abstract: We examined stock fecundity, abundance of eggs and larvae, and catch per haul of age 0 walleye pollock, Theragra chalcogramma, and considered the relationship between reproduction, recruitment and the ocean environment off the Pacific coast of northern Japan for the period between 1985 and 1996. To calculate stock fecundity, we estimated age at maturity and fecundity, and expanded estimates to the expected age composition of the population as estimated by Virtual Population Analysis. Eggs and larvae were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…In the case of pollock, year-class abundance was initially thought to be due to the environmental conditions experienced by eggs and larvae (Megrey et al 1996, Hamatsu et al 2004. Recent evidence suggests that environmental conditions can also mediate the influence of density-dependent processes occurring between the pollock egg and juvenile stages, and predators and water temperature can continue to modify abundance well into the juvenile stage (Bailey 2000, Ciannelli et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pollock, year-class abundance was initially thought to be due to the environmental conditions experienced by eggs and larvae (Megrey et al 1996, Hamatsu et al 2004. Recent evidence suggests that environmental conditions can also mediate the influence of density-dependent processes occurring between the pollock egg and juvenile stages, and predators and water temperature can continue to modify abundance well into the juvenile stage (Bailey 2000, Ciannelli et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…On assumption (i), FAO 21 have reported that walleye pollock reaches the first maturation at 3–4 years of age, 30–38 cm TL. Hamatsu and Yabuki 14 reported that 47–73% of the 4‐year‐old walleye pollock were mature in the Doto area, and Hamatsu 22 also reported that in 1990–1996 in the Doto area, about 80% of walleye pollock are observed as mature at 4 years old. Thus, it is natural to assume that 4‐year‐old fish mature and migrate to their spawning grounds.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, data collected in October were used for the analysis, as the spawning period extends from late November through late March in the northern Japan Sea population (Tsuji, 1990). For inter-population comparison, maturity parameters were taken from Stahl and Kruse (2008) in the two Bering Sea populations, Dorn et al (2010) in the Gulf of Alaska population and Hamatsu et al (2004) and Hamatsu and Yabuki (2007) in the Japan Pacific population. Identification of individual sexual maturity was based on the GSI in the Bering Sea populations, whereas the identification was based on the visual observation in the Gulf of Alaska population and the Japan Pacific population.…”
Section: Length and Age At Maturitymentioning
confidence: 99%
“…Length-fecundity relationships were taken from Hinckley (1987) in the Bering shelf population, Yanagimoto et al (2002) in the Bering basin population, Miller et al (1986) cited in Kendall and Nakatani (1992) in the Gulf of Alaska population, Hamatsu et al (2004) in the Japan Pacific population, and Zver'kova (1978) in the northern Japan Sea population. In the Bering basin population, remarkable changes in the length-fecundity relationship occurred with dramatic population declines between 1984 and 1999, but fecundity of spawners <450 mm did not change (Yanagimoto et al, 2002).…”
Section: Fecunditymentioning
confidence: 99%